Mildly reduced less defective graphene oxide/sulfur/carbon nanotube composite films for high-performance lithium–sulfur batteries. Issue 16 (6th April 2016) - Li, Rui; Zhang, Miao; Li, Yingru; Chen, Ji; Yao, Bowen; Yu, Mingpeng; Shi, Gaoquan
Abstract : Mildly reduced less defective graphene oxide (mrLGO) has a good conductivity and a high content of oxygenated groups, providing the freestanding mrLGO/S/CNT cathode with superior performance in Li–S batteries. Abstract : The microstructures and properties of the carbonaceous matrices in the cathodes of lithium–sulfur (Li–S) batteries have strong effects on their performances. We prepared a ternary composite cathode of mildly reduced less defective graphene oxide (mrLGO), sulfur, and carbon nanotubes (CNTs) by filtration for Li–S batteries. This battery showed a high initial specific capacity of 1219 mA h g −1 at 0.2 C and a stable specific capacity of around 1000 mA h g −1 after 200 cycles with a coulombic efficiency of 99%. Its excellent performance is mainly attributed to the good conductivity and residual oxygen containing groups of mrLGO, and the three-dimensional (3D) framework constructed using mrLGO sheets and CNTs.